STUDI KOMPARATIF PADA KOSTUM TARI MERAK KARYA RADEN TJETJE SOMANTRI DAN KARYA IRAWATI DURBAN ARDJO MELALUI PENDEKATAN ESTETIKA - Miraci Kartiyani (Universitas Komputer Indonesia, 2018)
West Java is one of the provinces that has a religious community with a wealth of cultural heritage and traditional noble values. As one example of the culture of West Java is dance, there are various kinds of dances in West Java. One dance that is widely known by the public is the Peacock Dance. The Peacock Dance is a dance originating from West Java and was created by Raden Tjetje Somantri in 1955. However, in contrast to the Peacock Dance that is often found today is the work of Irawati Durban which was remade costumes and choreography in 1965. Therefore researchers chose